Depression, anxiety and quality of life in patients with melanoma - Vojvodić, Aleksandra R; Dedić, Gordana (Vojnosanitetski pregled, 2021)
Background/Aim. Recent investigations have established a significant correlation between melanoma and quality of life, as well as anxiety and depression in these patients. In prognosis of melanoma, the most important is the stage in which it is diagnosed. The objective of the study was to analyze the quality of life, anxiety and depression in patients with a diagnosis of melanoma at different stages of the disease. Methods. In our cross-sectional study, 40 consecutive patients with melanoma, diagnosed and treated at the Department of Dermatology and Venerology, Military Medical Academy in Belgrade during the period from October to November 2015, were included. Twenty respondents were in stages I and II (localized disease) and 20 respondents in the stage IV (distant metastases). We used European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire (EORTC QLQ 30), Beck anxiety inventory (BAI) and Beck depression inventory (BDI). The statistical analysis included parametric and non-parametric descriptive statistics. Results. In patients with stages I and II of the disease, anxiety scores were higher in comparison to those in patients with the stage IV (37.5 vs. 14.5, respectively; p < 0.05), but depression was more pronounced (6 vs. 2.5, respectively; p < 0.05) in patients with the IV stage of the disease. There were statistically significant differences in all segments of quality of life between patients with stages I and II and those with the stage IV of the disease. The global quality of life was significantly worse in patients with the IV stage (33.5 vs. 83), the symptomatology was more pronounced (78.5 vs. 0) and the functioning was significantly worse (31 vs. 85) in relation to patients with stages I and II (p < 0.01) for all segments of quality of life. Conclusion. Anxiety and quality of life decrease, while depression increases with melanoma stages. The need for adequate social and family support as well as psychological assistance in order to achieve better coping with the illness are necessary in patients with melanoma. Further studies are needed for monitoring of anxiety, depression and quality of life from the moment of diagnosis of the disease over time, as well as the impact of new treatment modalities on these parameters.